Thermal properties of polyurethane elastomers from soybean oil-based polyol with a different isocyanate index. (March 2019) - Mizera, Kamila; Ryszkowska, Joanna
The aim of this work was to determine the influence of used soybean oil (SO)-based polyol on the thermal properties of tested polyurethane elastomers (PUEs), with a different value of isocyanate index (INCO ). The thermal properties determined by thermogravimetric analysis and differential scanning calorimetry show that the highest INCO causes an increase in hydrogen bonds in PUEs and higher thermal stability. A structural analysis and degree of phase separation (DPS) of the tested PUEs were carried out via Fourier transform infrared spectroscopy. This analysis showed that at INCO = 1.02, the largest number of urethane bonds arises in PUE. The physicomechanical properties of PUEs were also tested via density, resilience, hardness, and wear resistance. The results concluded that the increasing number of –NCO groups during production of PUEs with SO polyol changes the number of hydrogen bonds and DPS and causes the increase of properties such as thermal resistance, storage modulus, cross-linking density, and wear resistance.